Mapping the increasing sophistication of students' understandings of plate tectonics: A learning progressions approach. Issue 1 (2nd January 2019) - McDonald, Scott; Bateman, Kathryn; Gall, Helen; Tanis-Ozcelik, Arzu; Webb, Aubree; Furman, Tanya
Abstract: Plate tectonics is the organizing paradigm of geosciences, but it is also conceptually complex, and students often struggle with developing a system level understanding of the earth. This article reports on research designed to create a characterization of the different levels of sophistication around plate tectonics in the form of a learning progression for middle grades (grades 6–9). A learning progression is an educational research construct that can guide curriculum, assessment, and instruction by creating a description not just of students' misunderstandings but of a sequential pattern of increasingly sophisticated and productive student conceptions. This article reports on research findings from a 7-year National Science Foundation-funded project focused on the teaching and learning of earth and space science, which engaged in hundreds of conceptual interviews with students in diverse contexts across the state of Pennsylvania. This article focuses on the implications for higher education faculty in geosciences with regard to the preparation of students, the likely alternative conceptions they may hold, and hence instructional approaches to help their ideas mature toward a normative scientific understanding.